Extension on Symptom and Control of VSD Disease on Cocoa : Penyuluhan Gejala dan Pengendalian Penyakit VSD pada Tanaman Kakao - Parawansa, Ayu Kartini; McMahon, Peter J.; Aslam, Annisa Paramaswary; Aslam, Achmad Yassin Zidan Akram; Sombeng, Andi Rini Hastuti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The disease Vascular Streak Dieback (VSD) affects cocoa plants, causing symptoms such as necrotic streaks on leaves and branches. This disease can lead to a significant decrease in cocoa fruit production. Farmers in Anreapi face the challenge of protecting their cocoa plants from VSD, which threatens the long-term sustainability of their income by reducing harvest yields available for sale. The outreach method involves a series of steps to address partner issues, starting with preparation stages in Anreapi District. Subsequently, the socialization phase includes education on preventing and controlling VSD, and improving cocoa plant safety to support sustainable production and farmer income. Evaluation is conducted post-outreach to compare conditions before and after the outreach activities.